2016
DOI: 10.1186/s40814-015-0043-x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a stepped wedge cluster RCT and concurrent observational sub-study to evaluate the effects of modified ward night lighting on inpatient fall rates and sleep quality: a protocol for a pilot trial

Abstract: BackgroundFalls among hospitalised patients impose a considerable burden on health systems globally and prevention is a priority. Some patient-level interventions have been effective in reducing falls, but others have not. An alternative and promising approach to reducing inpatient falls is through the modification of the hospital physical environment and the night lighting of hospital wards is a leading candidate for investigation. In this pilot trial, we will determine the feasibility of conducting a main tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 71 publications
0
52
0
Order By: Relevance
“…Finally, the biggest strength of this study is the simplicity of the intervention, consisting only of a LED strip combined with a motion sensor. This study shows the potential of simple automated lighting interventions in fall prevention, which has been only studied to a limited extent [21,24,26,27].…”
Section: Limitations and Strengthsmentioning
confidence: 98%
See 3 more Smart Citations
“…Finally, the biggest strength of this study is the simplicity of the intervention, consisting only of a LED strip combined with a motion sensor. This study shows the potential of simple automated lighting interventions in fall prevention, which has been only studied to a limited extent [21,24,26,27].…”
Section: Limitations and Strengthsmentioning
confidence: 98%
“…Poor sleep quality has also been described as a risk factor for falls [22,23]. We hypothesized that Gight could im-prove sleep quality by obviating the need of overhead lighting [24] and by reducing fear at night. In our study, the positive effect of Gight on sleep quality was significant or showed a trend to positive effects in the single-item assessment.…”
Section: Sleep Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, the smaller number of night-time falls is likely partially attributed to less outdoor activity and does not necessarily indicate adequate lighting. Although some researchers expected better lighting to minimize falls [22], most studies have been performed only in indoor environments [23], and further research is needed on the relationship between lighting and falls.…”
Section: Discussionmentioning
confidence: 99%